2019
DOI: 10.1021/acs.est.8b06659
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and Synergic Production of Bioavailable Iron and Reactive Iodine Species in Ice

Abstract: The bioavailable iron is essential for all living organisms, and the dissolution of iron oxide contained in dust and soil is one of the major sources of bioavailable iron in nature. Iodine in the polar atmosphere is related to ozone depletion, mercury oxidation, and cloud condensation nuclei formation. Here we show that the chemical reaction between iron oxides and iodide (I–) is markedly accelerated to produce bioavailable iron (Fe­(II)aq) and tri-iodide (I3 –: evaporable in the form of I2) in frozen solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…[9] Such a freeze-concentration effect would increase the concentrations of reactants by several orders of magnitude compared to those in aqueous solution, which leads to the occurrence of chemical reactions that are negligible in water at room temperature. Similar accelerated reactions have been demonstrated in other systems, such as the oxidation of nitrite to nitrate and reduction of bromate, [10,11] which are all second order reactions with extremely low concentrations. [8] Coincidentally, the chemical degradation of MPs is a typical second order reaction induced by free radicals, [12] while the overall concentration levels of MPs in sea ice are generally not very high (38-234 particles/ m 3 ice), [6] which exactly match the characteristics of "freezing-accelerated" reactions.…”
Section: Microplasticssupporting
confidence: 73%
“…[9] Such a freeze-concentration effect would increase the concentrations of reactants by several orders of magnitude compared to those in aqueous solution, which leads to the occurrence of chemical reactions that are negligible in water at room temperature. Similar accelerated reactions have been demonstrated in other systems, such as the oxidation of nitrite to nitrate and reduction of bromate, [10,11] which are all second order reactions with extremely low concentrations. [8] Coincidentally, the chemical degradation of MPs is a typical second order reaction induced by free radicals, [12] while the overall concentration levels of MPs in sea ice are generally not very high (38-234 particles/ m 3 ice), [6] which exactly match the characteristics of "freezing-accelerated" reactions.…”
Section: Microplasticssupporting
confidence: 73%
“…When the ice temperature increases close to the melting point, a quasi-liquid layer (QLL) may form on the ice surface, as well as a liquid-phase compartment at the interface between the ice grain boundaries. ,, Such distinctly different microscopic environments of ice can act as a host for diverse types of reactions and have many interesting effects, such as accelerated reaction rates and new pathways due to the freeze-concentration effect in the liquid compartment, as well as the synthesis of new materials on the QLL-covered ice surface . These high-temperature chemical processes are important issues in environmental research related to terrestrial, oceanic, and atmospheric ices. ,, Such subjects are beyond the scope of the present review, and interested readers are referred to excellent reviews annotated above.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nitrite oxidizes to nitrate~1000 times faster in ice than in aqueous solution [17]. It is also reported that the dissolution of iron oxide to form soluble iron is significantly accelerated in ice, whereas such a reaction is negligible in aqueous solution [16,18]. These previous studies suggested that the enhanced dissolution of bioavailable iron is the result of a proton assisted reaction at the ice grain boundaries and the freeze concentration effect.…”
Section: Introductionmentioning
confidence: 97%